دراسة التنوع الفطري في ترب حقول منطقة الشير الساحلية المزروعة بالقمح وتأثير بعض الشروط البيئية في انتشار الأنواع - علي نوال; زريق نسيم; حسين ميادة (Latakia University Journal -Biological Sciences Series, 2019)
جمعت عينات التربة من منطقة الشير في محافظة اللاذقية خلال دورة سنوية كاملة 2009-2010 . عُزِلَ 1173 مستعمرة فطرية من 12 عينة تربة، وصنّفت في 37 جنساً و67 نوعاً تنتمي إلى: صف الفطريات البيضية Oomycetes (جنسين و5 أنواع)، صف الفطريات الإزدواجية Zygomycetes (4 أجناس و6 أنواع)، صف الفطريات الزقيةAscomycetes (4 أجناس و5 أنواع) ومن صف الفطريات الناقصة Deuteromycetes (27 جنساً و51 نوعاً). لوحظ سيادة كلٍّ من صف الفطريات الناقصة ومن ثمّ الإزدواجية، وتميزت بعض الأجناس مثل Aspergillus, Fusarium, Penicillium بوجودها شبه الدائم في جميع العينات المختبرة خلال فصول السنة، كما أظهرت النتائج تفاوتاً في معدل التردد والتنوع الفطري أثناء التغيرات الفصلية، فقد سجّل الحد الأعظم في فصل الخريف والأدنى في فصل الصيف. تم عزل ممثلين عن العديد من الأجناس الفطرية الممرضة مثل Alternaria , Curvularia ,Fusarium Helminthosporium, Nigrospora, Phytophthora, Pythium, Rhizoctonia, Sclerotium, Verticillium Soil samples were collected from Al-Sheer region in Lattakia province during annual cycle between 2009- 2010. 1173 fungal colonies were isolated from 12 soil samples, and classified into 37 genera and 67 species belonging to 2 genera and 5 species class Oomycetes, 4 genera and 6 species Zygomycetes, 4 genera and 5 species Ascomycetes, and 27 genera and 51 species Dueteromycetes. Results showed the dominance of class Dueteromycetes, followed by Zygomycetes, as well as the dominance of some genera such as Aspergillus, Fusarium, Penicillium which are characterized by their wide occurrence in all soil samples collected in the different seasons. Results also showed variation in the frequency average and fungal diversity during seasonal variation, where the highest frequency of fungal diversity recorded in Autumn while the lowest recorded in Summer season. The study showed several pathogenic fungi, such as Alternaria , Curvularia , Fusarium , Helminthosporium , Nigrospora , Phytophthora , Pythium , Rhizoctonia , Sclerotium , Verticillium.